The sources of O.M. Kovalevsky's Mongolian-Russian-French Dictionary - V.L. Uspensky (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The written sources of the Mongolian-Russian-French Dictionary (Dictionnaire mongol-russe-français) compiled by O.M. Kovalevsky (Józef Kowalewski) and printed in Kazan in 1844–1849 were considered. The research is highly relevant, because O.M. Kovalevsky himself did not clearly indicated the above-mentioned sources, especially those written in Asian languages. The fate of the unpublished Mongolian-Russian dictionaries by A. Igumnov, V. Novoselov, and Archimandrite Peter (Kamensky), all used by O.M. Kovalevsky, was traced. The titles of the dictionaries in Asian languages used by O.M. Kovalevsky and having only abbreviated titles were identified. The translation of a long Tibetan title of the Tibetan-Mongolian Dictionary used by O.M. Kovalevsky was provided. This title contains the name of its author (Lobsang-Galsang) and the name of the Buryat monastery where it was compiled (the Egituiskiy Datsan Monastery). O.M. Kovalevsky’s unpublished diaries stored at the National Archives of the Republic of Tatarstan and containing valuable information about the activities of P.L. Schilling von Canstadt in Siberia were analyzed. On P.L. Schilling von Canstadt’s initiative, a dictionary of Buddhist terms in three languages was engraved and printed. It was concluded that O.M. Kovalevsky’s dictionary embodied the most advanced achievements of contemporary Mongol studies and is based on a large number of written sources and dictionaries, both European and Asian.